Integrasi Prinsip Ekonomi Syariah dalam Penggunaan Digital Payment oleh Pelaku Usaha Mikro Kecil - Rifqi, Lathif Hanafir; Ana Zahrotun Nihayah; Siti Mujibatun (Jurnal Iqtisad, 2025)
Digitalization has become an integral part of modern financial management, including in supporting the operations of micro, small, and medium enterprises (MSMEs). This study aims to analyze the integration of Sharia economic principles in digital payment systems used by creative micro and small enterprises (MSEs) in Jepara Regency, Central Java. A qualitative approach was employed, incorporating in-depth interviews and literature reviews. Data were collected from seventeen MSEs that utilize digital payment platforms for business activities. The findings reveal that most MSMEs have adopted digital payment platforms, such as QRIS, GoPay, and OVO, to support their transactions. However, implementing Sharia principles, such as prohibiting gharar (uncertainty), maysir (gambling), and riba (usury), remains challenging. While awareness of the importance of Sharia principles is relatively high, limited Sharia financial literacy and lack of access to Sharia-compliant platforms hinder wider adoption. This study offers strategic recommendations, such as enhancing Sharia financial literacy, developing Sharia-compliant digital payment platforms, and fostering collaboration between regulators, service providers, and the Muslim community. Implementing these measures is expected to promote Sharia financial inclusion and strengthen Indonesia's Islamic economic ecosystem.